PENILAIAN EKONOMI EKOSISTEM MANGROVE DI KELUARAHAN KARANG REJO KOTA TARAKAN KALIMANTAN UTARA - Widya Novia Nitasari; Nurul Ovia Oktawati; Fitriyana (Jurnal Pembangunan Perikanan dan Agribisnis, 2016)
The purpose of the research is to identify the utilization of mangrove ecosystems by local society and analyzing economic value of mangrove ecosystems. Data were analyzied with the consumer surplus, travel cost method, benefit transfer, contingent valuation. The result obtained that the largest proportion of the value of mangrove ecosystems is the utilization value of turism as a direct benefit of Rp733.228.963.974,00 per year. While the largest proportion of the value non utilazion of mangrove ecosystems is the value of inheritance Rp 97.114.286,00 per year. Total of value of mangrove ecosystems of 22 hectare in Karang Rejo, Tarakan City North Borneo is Rp734.506.142.763,00 per year.